196: SARCOPENIA AND PATIENT'S BODY COMPOSITION: NEW MORPHOMETRIC TOOLS TO PREDICT CLINICAL OUTCOME AFTER IVOR-LEWIS ESOPHAGECTOMY. (23rd April 2022) - Battaglia, S; Cossu, A; Palumbo, D; De Pascale, S; Gualtierotti, M; Vecchiato, M; Parise, P; Puccetti, F; Barbieri, L; Elmore, U; De Cobelli, F; Fumagalli Romario, U; et al.
Abstract: Background and aim: Anastomotic leakage represents one of the most dreadful complications following esophagectomy. Although preoperative body composition has been identified as an independent predictor of prognosis for esophageal cancer patients after esophagectomy, its actual contribution to subsequent anastomotic leakage development is still unclear. The aim of the study was to further explore such a relationship. Methods: We conducted a multicenter retrospective study from a prospectively acquired database on consecutive patients who underwent Ivor Lewis esophagectomy in four italian high volume centers from May 2014. All patients who were evaluated with at least one preoperative CT scan were enrolled. Body composition parameters including total abdominal muscle area (TAMA), visceral fat area (VFA) and subcutaneous fat area (SFA) were determined based on two consecutive axial CT images extending upwards from the level of the third lumbar vertebra; sarcopenia was defined using predetermined sex specific values: 52.4 cm2/m2 for men, 38.5 cm2/m2 for women. Perioperative variables (ASA, neoadjuvant treatment, tumour site, anastomosis type were systematically collected. Results: 237 patients were enrolled. Preoperative BMI: 25.16 kg/m2; 23.6% of patients suffered from anastomotic leakage. According to CT morphometric assessment, 64.1% were classified as sarcopenic; these patients were more vulnerable in terms of postoperative death (within 90 days, P = 0.028). The mean VFA/TAMA and VFA/SFA ratios were 2.93 ± 1.87 and 0.93 ± 0.59, respectively. Both these ratios demonstrated a linear correlation with the Clavien Dindo classification of postoperative complications (R = 0.311 and 0.239, respectively); specifically, patients with anastomotic leakage had significantly higher VFA/TAMA (3.56 ± 1.86 vs. 2.75 ± 1.83, P = 0.006) and VFA/SFA (1.18 ± 0.68 vs. 0.87 ± 0.54, P = 0.003) ratios. In patients suffering from anastomotic leakage, the highest VFA/TAMA ratio values were found in those experiencing type III ( P = 0.044). No significant correlation was found between preoperative BMI and subsequent anastomotic leakage development ( P = 0.154). Conclusion: Analytical morphometric assessment represents a useful non invasive tool for preoperative risk stratification. The concurrent association of sarcopenia and visceral obesity seems to be the best predictor of anastomotic leakage, far better than simple BMI evaluation, and potentially modifiable if targeted with prehabilitation programs.